Design Coordination of a Fuzzy-based Unified Power Flow Controller with Hybrid Energy Storage for Enriching Power System Dynamics - Rajderkar, Vedashree P.; Chandrakar, Vinod K. (Engineering, Technology & Applied Science Research, 2023)
In power networks, operation planning has become necessary due to the continuously increased load demand. The Unified Power Flow Controller (UPFC) controls the power flow through the network and improves the dynamics of the power system. In this paper, the design application of the coordination of a fuzzy-based UPFC with hybrid energy storage has been proposed to enrich the system's dynamic performance during abnormal conditions and improve the hybrid energy storage performance during transients when the DC link voltage is insufficient to meet the converter voltage demand. The hybrid energy storage consists of a supercapacitor and a battery connected across the UPFC Vdc shunt capacitor. The proposed system to improve the UPFC performance during large disturbances on a multi-machine system was designed and tested in MATLAB/SIMULINK.